Schema-Based Instruction for Mathematical Word Problem Solving: An Evidence-Based Review for Students With Learning Disabilities. (May 2020) - Cook, Sara Cothren; Collins, Lauren W.; Morin, Lisa L.; Riccomini, Paul J.
The purpose of this review is to determine the evidence base classification of schema-based instruction (SBI) as an intervention to improve word problem-solving outcomes in mathematics for students with learning or mathematics disabilities in Grades K–12. Using the Council for Exceptional Children's quality indicators (QIs) and standards, we reviewed both single-case and group design studies to classify the evidence of SBI. Results of this review indicate that SBI is a potentially evidence-based practice (EBP) for students with learning disabilities. Implications and directions for research and practice are presented.